Morphological Analysis of Bronchial Arteries and Variants with Computed Tomography Angiography - Esparza Hernández, Claudia Nallely; Ramírez González, Juan Manuel; Cuéllar Lozano, Rolando Alberto; Morales Avalos, Rodolfo; González Arocha, Carla Sofía; Martínez González, Brenda; Quiroga Garza, Alejandro; Pinales Razo, Ricardo; Elizondo Riojas, Guillermo; Elizondo Omaña, Rodrigo Enrique; Guzmán López, Santos (2017)
The aim of our study was to determine the prevalence of anatomical variants of bronchial arteries using computed tomographic angiography in a population of northeastern Mexico. An observational, transversal, descriptive, comparative, retrospective study was performed using 139 imaging studies of Mexican patients in which we evaluated the following parameters from the left and right bronchial arteries: artery origin, branching pattern, arterial ostium, vertebral level of origin, diameter, and mediastinal trajectory. The anatomies of the bronchial arteries were similar in both genders, except distribution for vertebral origin level